Changing trends of HIV, syphilis, HCV infections and behavioural factors among female sex workers in Chongqing, China: findings from six serial surveillance surveys - Hu, Ling (BMJ Open, 2020)
OBJECTIVES: To explore the prevalence and changing trends of HIV, syphilis, hepatitis C virus (HCV) infections and risk behaviours among female sex workers (FSWs) and to provide reference and theoretical basis for formulating targeted interventions. DESIGN: Six consecutive cross-sectional surveys. SETTING: Chongqing, China. PARTICIPANTS: FSWs were included if they (1) were aged ≥16 years, (2) provided commercial sex for money or goods during the previous month and (3) were willing to participate in the survey and could provide verbal informed consent. This study included 16 791 of 16 810 participants recruited between 2013 and 2018. PRIMARY AND SECONDARY OUTCOME MEASURES: The prevalence of HIV/syphilis/HCV infection. RESULTS: The HIV and HCV prevalence among FSWs in Chongqing was stable during the study period, but the prevalence of syphilis had an increasing trend, particularly among low-tier and middle-tier FSWs. Improvements in HIV-related knowledge, condom use, injecting drug use and participation in HIV-related services were observed. However, no change was found in the prevalence of drug use. HIV infection was correlated with no condom use in the last commercial sex (adjusted OR (aOR) 3.48, 95% CI 1.90 to 6.37) and syphilis infection (aOR 4.88, 95% CI 1.95 to 12.18). Syphilis infection was correlated with inconsistent condom use (aOR 1.30, 95% CI 1.02 to 1.65), HIV infection (aOR 5.88, 95% CI 2.40 to 14.41), HCV infection (aOR 7.68, 95% CI 4.37 to 13.49) and sexually transmitted infection (STI) diagnosis in the past year (aOR 3.81, 95% CI 2.40 to 6.03). HCV infection was associated with injecting drug use (aOR 8.91, 95% CI 4.45 to 17.86) and syphilis infection (aOR 7.88, 95% CI 4.49 to 13.83). CONCLUSIONS: Comprehensive interventions targeting FSWs, particularly low-tier and middle-tier FSWs, should be increasingly implemented to prevent and control HIV, syphilis and other STIs.